2005
DOI: 10.1037/0278-7393.31.3.538
|View full text |Cite
|
Sign up to set email alerts
|

Labeling Bias and Categorical Induction: Generative Aspects of Category Information.

Abstract: When a person is characterized categorically with a label (e.g., Linda is a feminist), people tend to think that the attributes associated with that person are central and long lasting (S. Gelman & G. D. Heyman, 1999). This bias, which is related to category-based induction and stereotyping, has been thought to arise because a category label (e.g., feminist) activates the dominant properties associated with the representation of the category. This explanation implies that categorical information influences inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 123 publications
(299 reference statements)
5
31
0
Order By: Relevance
“…One source of this bias seems to come from the need to maintain cognitive economy [5]. One of the most compelling findings in the cognitive psychology of inductive inference is that people make a predictive inference on the basis of the categorical information that is immediately recognizable [6]- [10]. By arranging concepts categorically, we treat individual objects as a group and deal with the characteristics of the group as a whole, rather than individual objects separately.…”
Section: Discussionmentioning
confidence: 99%
“…One source of this bias seems to come from the need to maintain cognitive economy [5]. One of the most compelling findings in the cognitive psychology of inductive inference is that people make a predictive inference on the basis of the categorical information that is immediately recognizable [6]- [10]. By arranging concepts categorically, we treat individual objects as a group and deal with the characteristics of the group as a whole, rather than individual objects separately.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that categorical labeling such as in (9) bolsters the estimation of highly likely attributes (e.g., "KINATE contains no fat." see Gelman & Heyman, 1999;Walton & Banaji, 2004;Yamauchi, 2005). The main explanation suggested for this "labeling effect" is that categorical statements activate the underlying "content" of the category.…”
Section: Labeling Effect Generic Noun Phrases and Psychological Essementioning
confidence: 99%
“…The following examples help illustrate the design of the experiment (see Gelman & Heyman, 1999;Walton & Banaji, 2004;Yamauchi, 2005; for a similar procedure).…”
Section: Labeling Effect Generic Noun Phrases and Psychological Essementioning
confidence: 99%
“…We think that category labels play a guiding role in feature inference (E. M. Markman, 1989;Yamauchi, 2005;Yamauchi et al, 2007;Yamauchi & Markman, 2000) and promote a reasoning strategy using abstract rules (see Sloman, 1996, andSloman, 1994, for the distinction between rule-based and similarity-based reasoning strategies). First, participants' inferential projections should depend primarily on the matching/mismatching status of the labels when the two labels are characterized as the names of categories.…”
Section: Predictionsmentioning
confidence: 99%
“…These sentences roughly mean the same thing, but they evoke different kinds of implications. Gelman and Heyman (1999) suggested that categorical noun labels (e.g., "poem" in Sentence 1), unlike feature labels (e.g., "poetical" in Sentence 2), evoke a sense of immutability, endurance, and centrality linked to the identity of an object, even in 5-year-old children (see also Walton & Banaji, 2004;Yamauchi, 2005).…”
mentioning
confidence: 99%